Types, accuracy, and efficacy of salivary biomarkers in periodontal diagnosis - Munshi, Maha A.; Almozher, Hanan A.; Alqahtani, Fatimah A.; Youssef, Mohamed M.; Almtere, Abeer S.; Alsadoon, Basel K.; Alotheem, Lubna S.; Alhowirini, Lama F.; Alotaibi, Abdullah M.; Almutairi, Abdullah A.; Assiri, Ali H. (International Journal Of Community Medicine And Public Health, 2023)
Periodontal diseases primarily occur due, to infections and inflammation that affect the gums and bone structures supporting the teeth. In the stage, known as gingivitis the gums may become swollen turn red and bleed easily. These health issues not impact health but also have broader implications for overall well-being, including tooth loss, discomfort, bad breath and an increased vulnerability, to chronic illnesses. The main objective of this review is to examine aspects pertaining to diseases encompassing clinical indications, methods, for diagnosis, available treatment choices, and preventive strategies. This research meticulously examines the types of these diseases, their stages, and their causes. It also discusses the approaches and criteria used to diagnose these conditions. Additionally, the paper provides an evaluation of treatment alternatives and strategic frameworks, for managing pathologies. This includes both surgical approaches, well as supportive therapies. The paper emphasizes the importance of measures. Maintaining oral health through consistent dental hygiene practices, regular dental checkups, and necessary lifestyle adjustments. In conclusion, while periodontal diseases pose challenges in practice they can be controlled and prevented through collaboration, between dental practitioners, dental hygienists, and active patient participation.